Comment encourager la participation et l'autopromotion - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Appui à la participation et à l'autopromotion dans la gestion des ressources naturelles (1998) Coédition GTZ/Margraf Verlag Laudenbacher Strasse 9 97990 Weikersheim - ALLEMAGNE 239 pages, ISBN : 3-8236-1296-4 No CTA 909, 20 unités de crédit